Qualitative Investigation of the Singular Cauchy Problem F(t, x, x′) = 0, x(0) = 0 - Zernov, A. E.; Kuzina, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove the existence and uniqueness of a continuously differentiable solution with required asymptotic properties.